Antioxidant and hepatoprotective activities of Thai mango seed kernel extract - Saruth Nithitanakool (2018)
Three polyphenolic principles, 1,2,3,4,6-penta-Ogalloyl-β-D- glucopyranose (PGG), methyl gallate (MG), and gallic acid (GA), were isolated from the ethanolic extract of seed kernels of Thai mango (MSKE) (Mangifera indica L.cv. "Fahlun") and quantified using a TLC scanning densitometric method. The MSKE and its isolates were investigated by studying their antioxidant capacities using four different methods, by determining their in vitro anti-inflammatory activities, and by evaluating their hepatoprotective potential against liver injury in rats induced by carbon tetrachloride (CCl4). The hepatoprotective effect of MSKE is clearly supported by its polyphenolic nature of the main principle, PGG, which exhibited potent antioxidant and anti-inflammatory activities.